Development and characterization of cotton elastic yarns to improve wear comfort of bi-elastic thin fabrics - Broega, A. C. (2016)
Clothing is our second skin, beyond the aesthetic function it primarily has the protective function. One cannot speak about clothing design without mentioning comfort and we may even say that they are not dissociable. The clothing design, in conceptual sense, cannot be successful if it does not take into account the comfort component. Among the many comfort dimensions, the sensorial and ergonomic dimensions of comfort which influence the sensory perception and the ability of a garment to "well fit", are largely determined by the elastic properties of the yarns and fabrics. The present work, relates to the development of cotton elastic yarns for bi-stretch woven fabrics, designed for high-quality women's fine shirting. The yarns were manufactured by the conventional core-spinning method, using different filaments in the core and cotton fibres as sheath. The physical-mechanical properties of the yarns were evaluated to assess their performance ability to improve bi-stretch fabrics wear comfort.